Penentuan Kapabilitas Transfer Daya Listrik dengan Mempertimbangkan Stabilitas Tegangan Statis Menggunakan L Index - Al Imran Al Imran (Universitas Negeri Makassar, 2019)
The ATC determination method in this study uses line thermal constraints by calculating reactive power flow, and using Linear Power Transfer Distribution Factor. The ATC determination considers the magnitude of the voltage magnitude and the static voltage stability of each bus after the power transfer simulation is performed. Static voltage stability is calculated using the L Index. The results showed that the transfer of power equal to the ATC value in an electric power system caused a decrease in voltage stability or an increase in the L index value on the receiving bus on average 19 times the initial loading condition, even though it was still at a stable level. While the receiver bus voltage magnitude has decreased